Toe Walking as the Initial Symptom of a Spinocerebellar Ataxia 13 in a Patient Presenting with a Mutation in the KCNC3 Gene - Pomarino, David; Thren, Johanna Ronja; Thren, Anneke; Rostasy, Kevin; Schoenfeldt, Jan (Global Medical Genetics, 2021)
This article at hand described a 4-year-old child patient who initially presented with the symptoms of toe walking. As part of the diagnostic process, the patient was genetically tested to find the cause of the gait anomaly. The genetic test found a mutation in the KCNC3 gene. The variant c.1268G > A; p.Arg423. His was found in a heterozygotic state. This variant is frequently described as a cause for spinocerebellar ataxia type 13 (SCA13) in the literature. Apart from toe walking as the most pronounced symptom, the patient displayed an instable gait with frequent falls and delayed speech development. The genetic test to determine the cause of the gait anomaly successfully diagnosed the patient with a previously undiscovered SCA13 and subsequently enabled the recommendation of personalized further treatment.
Keywords: SCA 13; spinocerebellar ataxia 13; toe walking; idiopathic toe walking; habitual toe walking; genetic testing toe walking; pes cavus